Use of a competitive probe in assay design for genotyping of the UGT1A1*28 microsatellite polymorphism by the smart amplification process. (October 2007) - Watanabe, Jun; Mitani, Yasumasa; Kawai, Yuki; Kikuchi, Takeshi; Kogo, Yasushi; Oguchi-Katayama, Atsuko; Kanamori, Hajime; Usui, Kengo; Itoh, Masayoshi; Cizdziel, Paul E.; Lezhava, Alexander; Tatsumi, Kenji; et al.
A key feature of the smart amplification process version 2 (SMAP-2) is the ability to suppress mismatch amplification by using a unique asymmetric primer design and Thermus aquaticus MutS ( Taq MutS). However, we report here that use of SMAP-2 for polymorphism determination of the UGT1A1*28 allele required a further ancillary approach for complete background suppression. The UGT1A1*28 allele is a microsatellite copy number polymorphism. This is the first reported SMAP-2 assay designed for genotyping genetic variations of microsatellites. We found that by the addition of a primer to the amplification reaction, called a competitive probe (CP), assay specificity could be significantly enhanced. Including sample preparation time and use of a CP-enhanced SMAP-2 assay, we could rapidly detect the UGT1A1*28 polymorphism within 60 min. To test our method, we compared results from PCR sequencing and the CP-enhanced SMAP-2 assay on 116 human blood samples for UGT1A1*28 polymorphism and demonstrated perfect concordance. These results illustrate the versatility of SMAP-2 for molecular diagnostics and provide a new approach for enhancing SMAP-2 assay specificity.